Development and Performance Evaluation of a Semi-Automated Impact Fracture Tester - Oluyemi S. ONIFADE; Olusegun O. AJIDE (FUDMA Journal of Engineering and Technology, 2026)
To evaluate the mechanical properties of metals and non-metals - such as tensile strength, compression, hardness, fatigue, flexural, and torsional strength - several standardized tests are used, and impact strength testing is essential for assessing the functionality, longevity, and safety of materials under abrupt loads. Izod impact testing, an ASTM standard method, is commonly used to assess the impact resistance of materials by measuring the energy absorbed during fracture. However, an affordable, locally manufactured substitute is required due to the high cost and unreliability of imported impact fracture testers. The design, construction, and testing of an Izod-based impact fracture tester created to examine the fracture properties of alloys under high strain rates are presented in this research. The machine consists of five primary components: a rigid frame, a pendulum hammer, a specimen clamp, a base, and a semi-automated digital display for data acquisition. After fabrication, the machine was tested and its performance evaluated by comparing its results with those from a standard testing machine. Three materials - Mild Steel, Aluminum, and High-Density Polyethylene (HDPE) - were selected to represent a spectrum of mechanical properties and fracture behaviors. Each specimen was machined to standard dimensions and tested in triplicate to ensure consistency. The primary evaluation metric was the energy absorbed until fracture, indicating the material’s toughness. The fabricated machine demonstrated satisfactory performance, achieving a maximum energy of 58.41 J at a pendulum velocity of 3.9 m/s. The test results confirmed the effectiveness of the machine in assessing material toughness under high strain rates.